Cyberbullying in a Multicultural Context—Forms, Strain, and Coping Related to Ethnicity-Based Cybervictimization - Schultze-Krumbholz, Anja; Pfetsch, Jan S.; Lietz, Katrin (Frontiers in Communication, 2022)
Cyberbullying is repeated aggression via digital media. There is extensive research analyzing forms of cyberbullying (e.g., relational or picture-based cyberbullying) and coping reactions (e.g., passive coping, seeking social support, retaliation). However, the mechanisms of cyberbullying in a multicultural society are not well-understood yet. Studies from the US show lower rates of cybervictimization for ethnic minorities, but comparable outcomes, studies from outside the US show different results. The present study focuses on the prevalence of ethnic/racist motives for cybervictimization as compared to non-ethnic/racist motives among adolescent students in a sample from Germany. Moreover, this study examines whether students with a migration background experience more strain and employ the same coping strategies as students without a migration background. An ethnically diverse sample of N = 348 adolescents, aged M = 14 (SD = 1.2) years, 50% males, completed a questionnaire about cyberbullying, perceived strain, motives for cybervictimization and coping behavior. 21% of the sample had no, 14% had a first-generation, and 66% had a second-generation migration background. Adolescents with a migration background generally reported higher levels of all victimization motives. No difference in perceived strain was found between the migration status groups. Ethnicity-based motives only significantly predicted ethnic/racist victimization, while dispute-related motives predicted all types of cybervictimization. First-generation migration background, ethnicity-based cybervictimization and perceived strain all played an important role in the different coping strategies. In sum, ethnic/racist cybervictimization seems prevalent especially among first generation adolescents, who are affected in a comparable manner as non-immigrants. Adolescents with a first-generation migration background seem to be especially vulnerable. Prevention and intervention efforts should focus on functional coping strategies especially for this group on the one hand. On the other hand, evidence-based intervention programs should be implemented to reduce bias and ethnicity-/race-based perpetration and victimization to foster successful acculturation and integration.